The entrainment cycle: Understanding professionals’ compliance with extreme work hours in professional service firms - Lupu, Ioana; Liu, Shanming (Accounting, Organizations and Society, 2025)
Extreme work hours in professional service firms (PSFs) are often attributed to organizational control mechanisms such as time sheets, utilization targets, and performance evaluations. This paper introduces the concept of the entrainment cycle to explore how these controls foster professionals' compliance with extreme work patterns. The entrainment cycle explains how individuals become continuously synchronized with the collective rhythm of the organization. Drawing on 159 interviews with 81 professionals across two PSFs, the study explores how formal and normative controls synchronize individuals with the fast-paced organizational tempo. The findings reveal how bureaucratic and cultural entrainment mechanisms contribute to synchronization. Moreover, emotions and bodily responses play a critical role in making professionals internalize the organization's rhythms. Periods of synchronization trigger positive feedback loops in which heightened emotions and bodily responses reinforce individuals' attachment to work. These synchronized periods contrast with moments of desynchronization in which professionals experience negative feedback loops characterized by guilt, anxiety, and physical withdrawal symptoms. The bodily and emotional mechanisms this study reveals reinforce professionals' synchronization with collective rhythms, locking them into an entrainment cycle that perpetuates long hours and ever-intensifying work. This study offers new insights into how controls affect individuals and organizations in significant, far-reaching, and often unobtrusive ways.